2012
DOI: 10.1007/s00259-012-2276-8
|View full text |Cite
|
Sign up to set email alerts
|

European multicentre database of healthy controls for [123I]FP-CIT SPECT (ENC-DAT): age-related effects, gender differences and evaluation of different methods of analysis

Abstract: This study provides a large database of [(123)I]FP-CIT SPECT scans in healthy controls across a wide age range and with balanced gender representation. Higher DAT availability was found in women than in men. An average age-related decline in DAT availability of 5.5 % per decade was found for both genders, in agreement with previous reports. The data collected in this study may serve as a reference database for nuclear medicine centres and for clinical trials using [(123)I]FP-CIT SPECT as the imaging marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
187
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(221 citation statements)
references
References 26 publications
20
187
3
4
Order By: Relevance
“…SBR values are commonly in the range [0. 5,4], and in line with our observations with PPMI data, previous work has shown that these values can differ substantially across sites [5,6]. We have demonstrated that our method restricts the quantification to values in the interval [0, 1] independently of the camera and diminishes the intensity differences across SPECT devices.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…SBR values are commonly in the range [0. 5,4], and in line with our observations with PPMI data, previous work has shown that these values can differ substantially across sites [5,6]. We have demonstrated that our method restricts the quantification to values in the interval [0, 1] independently of the camera and diminishes the intensity differences across SPECT devices.…”
Section: Discussionsupporting
confidence: 75%
“…This is due to the fact that the intensity profile of this type of images heavily depends on a variety of factors including acquisition hardware and settings, reconstruction algorithm and physiological-related factors, such as age, gender, and metabolism [5,7]. This is illustrated in Fig.…”
Section: Dat Spect Intensity Profilementioning
confidence: 99%
See 2 more Smart Citations
“…All subjects had dopaminergic imaging with either 123I Ioflupane targeting the dopamine transporter (DAT‐SPECT) or 18F AV133 (Australian site only) targeting the vesicular monoamine transporter (VMAT‐PET) at screening according to the imaging technical operations manual (www.ppmi‐info.org) 20, 21, 22, 23, 24. To ensure technical standardization across multiple sites and cameras employed in this study, a central core imaging laboratory developed a program for technical qualification, quality assurance, and ongoing camera quality control.…”
Section: Methodsmentioning
confidence: 99%